Low-cost carbon sources for the production of a thermostable xylanase by Aspergillus niger - Ana Cláudia Elias Pião Benedetti; Eliana Dantas da Costa; Caio Casale Aragon; Andréa Francisco dos Santos; Antônio José Goulart; Derlene Attili-Angelis; Rubens Monti (Revista de Ciências Farmacêuticas Básica e Aplicada, 2013)
A strain of the filamentous fungus Aspergillus niger was isolated and shown to possess extracellular xylanolytic activity. These enzymes have biotechnological potential and can be employed in various industries. This fungus produced its highest xylanase activity in a medium made up of 0.1% CaCO3 , 0.5% NaCl, 0.1% NH4 Cl, 0.5% corn steep liquor and 1% carbon source, at pH 8.0. A lowcost hemicellulose residue (powdered corncob) proved to be an excellent inducer of the A. niger xylanolytic complex. Filtration of the crude culture medium with suspended kaolin was ideal for to clarify the extract and led to partial purification of the xylanolytic activity. The apparent molecular mass of the xylanase was about 32.3 kDa. Maximum enzyme activity occurred at pH 5.0 and 55-60ºC. Apparent Km was 10.41 ± 0.282 mg/mL and Vmax was 3.32 ± 0.053 U/mg protein, with birchwood xylan as the substrate. Activation energy was 4.55 kcal/mol and half-life of the crude enzyme at 60ºC was 30 minutes. Addition of 2% glucose to the culture medium supplemented with xylan repressed xylanase production, but in the presence of xylose the enzyme production was not affected.